New Queer Cinema and Lesbian Films - Pick, Anat (New Queer Cinema: A Critical Reader, 2004)
The immediate aim of this chapter is to provide a critical overview of the place of lesbian films within New Queer Cinema. The task is not an easy one in a field which is as contentious as it is broad. The main difficulty seems to be how best to approach a range of definitions, from ‘new’ to ‘queer’ to ‘lesbian’, since with every one of them, we risk biting off more than we can chew. As often happens with formal titles, so with the New Queer Cinema, its lifespan (‘officially’ 1992-2000) now seems to have been a great deal shorter
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Europe (lieu de production du savoir); _Nettoyé

Examining Professional and Academic Culture in Chilean Journalism and Mass Communication Education - Mellado, Claudia (Journalism Studies, 2011)
This article discusses key findings from a survey of the professional patterns, scholarly productivity, and educational characteristics of Chilean Journalism and Mass Communication (JMC) educators, as well as documentary information about the schools where they work. The results reveal a weak academic culture that contrasts with a strong professional culture among the members of this community, but also the influence that both organizational and individual variables have on Chilean JMC educators' orientations. Specifically, the analyses indicated that the level of education, part-time/full-time commitment, and the type of university are the most influential factors in defining both the prevalence of a professional culture and the lack of research productivity. These findings support other international studies, indicating a global tendency across key variables that influence academic development in the field. Likewise, it shows how distant Chilean JCM educators are from the university-scholarly tradition.
Keywords: 2-Analyses formalistes; 2-Approches sociologiques; 2-Étude des industries culturelles; 3-Amérique du Sud (corpus analysé); 4-Europe (lieu de production du savoir); _Nettoyé

De- Westernizing Media Theory to Make Room for African Experience - Nyamnjoh, Francis B. (Popular Media, Democracy and Development in Africa, 2010)
How should one think about popular media in the African context? Should we attempt to understand and analyse the increasing proliferation of tabloids, reality television shows, pop music, websites and mobile communications through the analytical frameworks constructed by scholars in the Global North, or does Africa pose unique research questions? Is there a danger of either essentializing Africa by treating her as ‘different’, or by ignoring her specificity by approaching her media via Western theoretical constructs? The scholar wishing to understand the interface between popular media, development and democracy in contemporary African societies is faced with a complex double bind. Elsewhere (Nyamnjoh 2005: 2-3) I have argued that African worldviews and cultural values are doubly excluded from global media discourses, first by the ideology of hierarchies and boundedness of cultures, and second by cultural industries more interested in profits than the promotion of creative diversity and cultural plurality. Little attention is accorded to how Africans negotiate and navigate the various identity margins and cultural influences in their lives, in ways that are not easily reducible to simple options or straightforward choices. The consequence of rigid dichotomies or stubborn prescriptiveness based on externally induced expectations of social transformation is an idea of democracy hardly informed by popular articulations of personhood and agency in Africa, and media whose professional values and content are not in tune with the expectations of those they purport to serve. The predicament of media practitioners in such a situation, as well as those wishing to understand African media practice through media theory, is obvious: to be of real service to liberal democracy and its expectations of modernity, they must ignore alternative ideas of personhood and agency in the cultural communities within which such practices take place and of which such practitioners and, often, scholars form part. Attending to the interests of particular cultural groups as strategically essential entities risks contradicting the principles of liberal democracy and its emphasis on civic citizenship and the autonomous individual, which media practitioners in African societies are being held accountable to.
Keywords: 1-Cinéma; 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 3-Afrique (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice noir.e; 5-Identités diasporiques; _Nettoyé

Transnational Communication as Deliberation, Ritual, and Strategy - Brüggemann, Michael; Wessler, Hartmut (Communication Theory, 2014)
Globalized communication flows transcend and transform national borders. Transnational media outlets targeting audiences around the globe, issues of global concern are subjected to border-crossing public debates, media events receive transnational attention, and public diplomacy efforts succeed—and fail—in characteristic patterns around the world. In response to these phenomena the article shows how the study of transnational communication can benefit from combining 3 theoretical perspectives that are rarely studied together: communication as deliberation, as ritual, and as strategy. Particularly in explaining the failures of transnational communication, explanatory potential often seems to lie just outside the limited vision of each of the 3 perspectives—and outside the scope of empirical analyses that are limited to Western contexts.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 4-Europe (lieu de production du savoir); _Nettoyé

“Citizen Journalism” in the Syrian Uprising: Problematizing Western Narratives in a Local Context - Al-Ghazzi, Omar (Communication Theory, 2014)
This article analyzes the term ‘citizen journalism’ against the backdrop of the Arab uprisings in order to show how it overlooks the local context of digital media practices. The first part examines videos emanating from Syria to illustrate how they blur the lines between acts of witnessing, reporting, and lobbying, as well as between professional and amateur productions, and civic and violent intentions. The second part highlights the genealogies of citizenship and journalism in an Arab context and cautions against assumptions about their universality. The article argues that the oscillation of Western narratives between hopes about digital media's role in democratization in the Arab World and fears about their use in terrorism circumscribe the theorization of digital media practices.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); 5-Identités diasporiques; _Nettoyé

The Other in South Asian Religion, Literature and Film: Perspectives on Otherism and Otherness - Dimitrova, Diana (Routledge, 2013)
This book introduces the term "otherism" and looks at the discourse of otherism and the issue of otherness in South Asian religion, literature and film. It examines cultural questions related to the human condition of being the "other," of the process of "othering" and of the representation of "otherness" and its religious, cultural and ideological implications. The book applies the perspectives of ideological criticism, theories of hybridity, orientalism, nationalism, and gender and queer studies to gain new insights into the literature, film and culture of South Asia. It looks at the different ways of interpreting "otherness" today. The book goes on to analyze the ideological implications of the creation of "otherness" with regard to religious and cultural identity and the legitimation of power, as well as how the representation of "otherness" reflects the power structures of contemporary societies in South Asia. Offering a well-thought-out reflection on important cultural questions as well as a deep insight into the study of religion and "otherness" in South Asian literature and film, this book is a pioneering project that is of interest to scholars of South Asian Studies and South Asian religions, literatures and cultures.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); 5-Identités diasporiques; _Nettoyé

ALT 36: Queer Theory in Film and Fiction: African Literature Today - Emenyonu, Ernest N.; Hawley, John C. (Boydell & Brewer, 2018)
"Debates on the future of the African continent and the role of gender identities in these visions are increasingly present in literary criticism forums as African writers become bolder in exploring the challenges they face and celebrating gender diversity in the writing of short stories, novels, poetry, plays and films. Controversies over the rights of Lesbian, Gay, Bisexual, Trans, Intersex, Queer (LGBTIQ) communities in Africa, as elsewhere, continue in the context of criminalization and/or intimidation of these groups. Residual colonial moralizing and contemporary western identity norms and politics vie with longstanding polyvalent indigenous sexual expression. In addition to traditional media, the new social media have gained importance, both as sources of information exchange and as sites of virtual construction of gender identities. As with many such contentious issues, the variety of responses to the "state of the question" is strikingly visible across the continent. In this issue of ALT, guest editor John Hawley has sampled the ongoing conversations, in both African writing and in the analysis of contemporary African cinema, to show how queer studies can break with old concepts and theories and point the way to new gender perspectives on literary and cinematic output. This volume also includes a non-themed section of Featured Articles and a Literary Supplement."--Publisher's description
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice noir.e; 5-Créateur.rice LGBTQ+; 5-Identités diasporiques; _Nettoyé

Lesbian Cinema after Queer Theory - Bradbury-Rance, Clara (Edinburgh University Press, 2019)
The unprecedented increase in lesbian representation over the past two decades has, paradoxically, coincided with queer theory’s radical transformation of the study of sexuality. In Lesbian Cinema after Queer Theory, Clara Bradbury-Rance argues that this contradictory context has yielded new kinds of cinematic language through which to give desire visual form. By offering close readings of key contemporary films such as Blue Is the Warmest Colour, Water Lilies and Carol alongside a broader filmography encompassing over 300 other films released between 1927 and 2018, the book provokes new ways of understanding a changing field of representation. Bradbury-Rance resists charting a narrative of representational progress or shoring up the lesbian’s categorisation in the newly available terms of the visible. Instead, she argues for a feminist framework that can understand lesbianism’s queerness. Drawing on a provocative theoretical and visual corpus, Lesbian Cinema after Queer Theory reveals the conditions of lesbian legibility in the twenty-first century.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 4-Europe (lieu de production du savoir); 5-Créateur.rice LGBTQ+; _Nettoyé